Perbandingan Metode Ekstraksi DNA pada Tanaman Ulin (Eusideroxylon zwageri) - Ridzqya, Salsabila Al Alya; Polosoro, Aqwin; Enggarini, Wening; Kusumanegara, Kusumawaty; Helmanto, Hendra; Magandhi, Mahat; Satyawan, Dani; Hadiarto, Toto; Yuniaty, Alice (Innovation Centre for Tropical Sciences, 2024)
DNA isolation is a routine procedure in molecular analysis. The method of plant genome DNA extraction has been widely available throughout global laboratories. Several labs made some modifications to obtain optimal results. This research was aimed to analyse two types of DNA extraction methods for ironwood plant (Eusideroxylon zwageri), one tropical rain forest woody plant known for its high strength and durability. The results indicate that isolation DNA kit produced high DNA purity with lower concentrations while CTAB methods generated lower DNA purity with higher concentrations. This may be used as consideration of DNA isolation for downstream molecular analyses. Keywords: DNA extraction, ironwood, CTAB, genomic DNA